PERILAKU CAMAT DALAM PELAKSANAAN PNPM MANDIRI DI KECAMATAN PUTUSSIBAU UTARA KABUPATEN KAPUAS HULU - Tia Arniyati Permatasari E.42009036 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2021)
The Process of Writing this inscription is intended to identify the behavior of districk in the execution of Rural Autonomous National Programme for Society Empowerment in North Putussibau Districk which is observed from the behavior of Spreading information, consultation and delegation, planning and organizing, and monitoring the programme. The title is choosen based on issue related to the programme about arrears in money from Saving and Lending for Women. Whereas the monitoring is alone correctly. This study uses a descriptive type of research with a qualitative approach. Collecting data uses interview technique and documentation. Subjects of the research are head of districk, head of economic and development section, Programme Executor Unit in North Putussibau Districk and me of the citizen who is choosen purposively. The conclusion of this study is behavior of Head of Districk which is applied in the execution of Rural Autonomous National Programme for Society Empowerment has gone on well, but there’s an obstacle that is caused by people in arrears from the programme of Saving and Leading for Women. That’s why, Head of Districk as the highest leader in districk has to do more intensive and firm monitoring in order to unit the arrears in the execution of Rural Autonomous National Programme for Society Empowerment. Keywords :    Behavior of Head of Districk, Leadership, Firmness, and The executor of  Rural Autonomous National Programme for Society Empowerment.